Nanoliposomal ceramide prevents in vivo growth of hepatocellular carcinoma. Issue 5 (30th December 2010) - Tagaram, Hephzibah Rani S; DiVittore, Nicole A; Barth, Brian M; Kaiser, James M; Avella, Diego; Kimchi, Eric T; Jiang, Yixing; Isom, Harriet C; Kester, Mark; Staveley-O'Carroll, Kevin F
Abstract : Background and objectives: Hepatocellular carcinoma (HCC) affects an increasing number of people worldwide. The poor survival rate of patients with HCC is manifested by an aggressive and metastatic phenotype, as well as a poor response to common therapeutic strategies. The purpose of this study was to evaluate the efficacy of nanoliposomal C6-ceramide as an antineoplastic agent in an in vivo model of human HCC. Methods: The growth-arresting and pro-apoptotic properties of nanoliposomal C6-ceramide were first evaluated in vitro in human SK-HEP-1 cells by assessing cellular viability, caspase 3/7 activity, annexin-V expression, DNA fragmentation, cell cycle distribution and AKT phosphorylation. SK-HEP-1 cells were then engrafted subcutaneously into athymic nude mice and nanoliposomal C6-ceramide was administered by tail vein injection. Tumour size was monitored over time, followed by excision of tumours to evaluate tumour vascularisation, proliferation, apoptosis and cellular signalling. Results: Nanoliposomal C6-ceramide, but not ghost (no ceramide) nanoliposomes, induced apoptotic cell death of SK-HEP-1 cells in vitro, concomitant with an accumulation of cells in the G2 phase of the cell cycle and decreased phosphorylation of AKT. Systemic administration of nanoliposomal C6-ceramide to mice engrafted with SK-HEP-1 tumours reduced tumour vascularisation and proliferation, induced tumour cell apoptosis, decreased phosphorylation of AKT and ultimately blocked tumour growth. Conclusions: These studies show that nanoliposomal ceramide is an efficacious antineoplastic agent for the treatment of in vitro and in vivo models of human HCC.